Foot shape and its relationship with somatic characteristics in pre-school children - Puszczałowska-Lizis, Ewa; Ciosek, Justyna (Medical Studies/Studia Medyczne, 2017)
Introduction : The preschool period, characterised by high intensity of ontogenetic developmental changes, is considered to be the most important regarding formation of the foot. Getting to know the issue of the foot anatomy in children in this period is the main problem, which is the starting point towards proper prevention, examination, or correction of its deformities. Aim of the research: To analyse the shape of children’s feet and its relationship with chosen somatic characteristics in pre-school children. Material and methods : The study group comprised 80 five-year-old children recruited from randomly selected pre-schools in the Podkarpackie region. A CQ-ST podoscope was used as the research tool. In order to evaluate intersex differences at the average level of the tested variables, we used the Student’s t test or alternatively the Mann-Whitney U test. The relations between tested variables was assessed using Pearson’s linear correlation or Spearman’s rank correlation. Results : A low percentage of foot deformities in the children was found. In girls, statistically significant relationships were seen between Clarke’s angle in the right foot and body mass index as well as between Wejsflog index in the right foot and body weight and height. In the case of boys, Clarke’s angle and Wejsflog index in the left foot correlated with body mass index. Conclusions: We can therefore assume that most of the surveyed girls and boys had correctly longitudinally and transversely arched feet and toes positioned correctly. Excessive weight was a factor distorting the foot shape in children; it caused a deterioration of longitudinal and transverse arch of the right foot in girls, and left foot flattening occurred in boys.